Criteria adopted by dentists to indicate the extraction of periodontally involved teeth - Carlos Heitor Cunha Moreira; Fabricio Batistin Zanatta; Raquel Antoniazzi; Priscila Ceolin Meneguetti; Cassiano Kuchenbecker Rösing (University of São Paulo, 2007)
When dealing with patients with periodontal disease of variable severities, dentists must often choose between treating and restoring the involved tooth or indicating its extraction. Different criteria have been adopted in this decision-making process. The purpose of this study was to evaluate the criteria adopted by dentists to indicate the extraction of teeth with periodontitis. Dentists were interviewed at their private practices in three cities of the state of Rio Grande do Sul, Brazil. The evaluated criteria included severity of attachment loss, tooth mobility, furcation involvement, prosthetic planning, periodontal-endodontic lesion, possible systemic involvement due to the presence of periodontitis, referral to a periodontist for evaluation, radiographic bone loss greater than 50%, presence of extensive caries, socio-economic and cultural status of the patient, among others. The most often adopted criteria to indicate the extraction of periodontally affected teeth were the presence of mobility (37.5%), severity of attachment loss (24.3%) and radiographic bone loss greater than 50% (21.2%). The results of the present study demonstrated the difficulties faced by dentists to indicate the extraction of teeth with severe attachment loss, in addition to the establishment of an adequate prognosis. Aspects associated with the past disease were still the most often reported to indicate the extraction of teeth for periodontal reasons.